"Atmosphère, atmosphère": On the Study of France Between the Wars - Steven Ungar (Studies in 20th & 21st Century Literature, 1997)
Street Noises: Parisian Pleasure, 1900-1940 by Adrian Rifkin and Shanghai on the Métro: Spies, Espionage, and the French Between the Wars by Michael B. Miller are test cases for issues of historiography related to period and duration in the study of France between 1919 and 1940. Of added relevance to these issues is the fact that Rifkin and Miller both question distinctions between elite literary cultures linked to book publishing and new forms of mass reproduction enhanced by technologies of sound reproduction and illustration. A concluding excursus explores recent theories of urban space symbolized by the street as a site of interaction and exchange.
Keywords: " Street Noises: Parisian Pleasure; 1900-1940" Adrian Rifkin; " Shanghai on the Métro: Spies; Espionage; and the French Between the Wars" Michael B. Miller; historiography; period; duration; France; French; between1919 and 1940; 1919; 1940; distinction; elite literature; elite literary cultures; culture; book publishing; mass production; mass reproduction; sound reproduction; illustration; urban space; symbolize; street; site of interaction; exchange